Technique for Characterization and Clearance of the Resin Waste from the Greek Research Reactor (GRR-1) - Ntalla, E.; Savvidou, A. (HNPS Advances in Nuclear Physics, 2019)
The present work concerns the examination of management options for VLLW drums [1] with ion exchange resin waste from the Greek Research Reactor (GRR-1). According to the general clearance criterion [2, 3], after cementation, 75 % of the VLLW could be cleared and for the remaining 25 % the summation formula result is lower than 1.6. The proposed management option for the total amount of the VLLW resin is the spread of the cemented resin, before thickening, over the ground around the interim storage facilities, inside the controlled area, for pavement construction. Additionally, a quantity of the cemented waste will be used for preparation of blocks for quality and homogeneity examination of the waste form.